School Principal Change Management: Case Study at Madrasah Tsanawiyah Post the COVID-19 Pandemic - Fatimah, Anisa (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to develop the role of the principal as a leader in managing change in Madrasah Tsanawiyah in the new normal era. The research method used is descriptive qualitative, with a case study model conducted at Mts Negeri 5 Sleman, Yogyakarta. The data collection techniques are literature review and in-depth interviews with the head of the deputy head of madrasah in the field of HRD. The results showed that the role of the madrasa principal in managing change in learning in the new normal era was to make planned changes, namely through the exploration, planning, action, and integration stages. The principal regularly monitors planned changes in the hybrid learning model and repeatedly predicts and controlled so that learning objectives are achieved effectively and efficiently. The steps for implementing the hybrid learning model held by MTs Negeri 5 Sleman is combining four methods, they are face-to-face learning in laboratory or classroom, synchronous virtual collaboration by Microsoft 365, asynchronous virtual collaboration by Google classroom to answer quiz, and self-paced asynchronous by Whatsapp group. The implication of the role of the Madrasa principal in managing change in learning is to increase digital literacy for teachers and students and make technology a learning partner in the Madrasa environment.